Development of Corporate Social Responsibility Theories - Juščius, Vytautas (Ekonomika, 2007)
Recently, the issues of social responsibility of business in the US and EU states have been extensively addressed not only by researchers, but also by CEOs of enterprises, politicians, executive governmental authorities, trade unions, non-governmental organisations. This can be judged from the increasing number of publications on this issue as well as states’ governmental acts passed to initiate and encourage corporate social responsibility initiatives. The article deals with the development of social responsibility of business in the context of the prevailing economic and manageral theoretical models. Although the concept of corporate social responsibility has been developed in the second half of the 20th century, the social role of business has been mentioned in the English classical political economy research studies. We can state that A. Smith and D. Richard essentially formulated the elements of the concept of corporate social responsibility in business operating within the free competition scheme. K. Marx’s theoretical models provide a specific conception of social responsibility, which is actually radically different from that of the classical English political economy approach. Through imposing the value added production function to the capital and by giving its critical assessment, Marx presented his interpretation of social responsibility of both market economy and of alleged public limited company. An important stage in the corporate social responsibility study was the introduction and promotion of stakeholders theory which was reviewed in detail by R. Freeman in his monograph in 1984. He then modified a conventional corporation input-output model which accepted only four groups of players as directly linked to the firm’s activity: shareholders, workers, suppliers and customers, by expanding the influences’ list to governmental bodies, political groups, trade associations, trade unions, communities, associated corporations, environmentalists, human and customer rights’ proponents and other vested parties whose interests are important to business and undertakings. Stakeholders theory admits the importance of corporate responsibility and the necessity of related costs. It maintains that the support of stakeholders adds to formation of a firm-friendly environment and positively affects a firm’s operation results. Despite its popularity, stakeholders theory however failed the overall unconditional acclaim and has been subject to criticism both in the theoretical and empirical aspects. Corporate social responsibility analysis has been closely related to strategic corporate governance issues. This is obviously featured in a rather popular resource-based view model. The model maintains that every firm possesses a unique specific combination of resources and competences. Should these resources and capacities prove to show indeed valued, unique, rare and indispensable, they can actually make for the exclusive competitive advantage to the firm. Certainly, companies strive to identify, sustain and develop this advantage. Modem society shows an obvious growing influence of corporate social responsibility supporters. It shoved be noted that stakeholders, who a couple decades ago used to demand managerial social responsibility, sought arguments in the defence of their positions primarily in the ethics research works. Lately there has been a general tendency to justify the social responsibility of business on the account of financial benefit consideration. Also, an important thing is that even amongst the conventional neoclassical economic scholars increasing are studies that attempt to justify the costs of corporate social programmes through revealing their efficiency on a long-term scale. As a joint-point to enable incorporation of social expenses in the neoclassical profit maximisation model, the conception of strategic investment has been used lately. Classical enterprise theory makes impossible the maximization of the two values simultaneously - the profit and social benefit. Some researchers, however, through the use of traditional macroeconomic analysis instruments, seek to prove that corporate social programmes should be approached as strategic investment. In this respect, the dimensions of profit and social responsibility maximisation coincide. In Lithuania, corporate social responsibility has been mostly assessed in the context of human resource theory. Empiric analysis in the field remains in its initial stage.